Environmental orientation among nascent and established entrepreneurs: an empirical analysis of differences and their causes. (2nd August 2019) - Hörisch, Jacob; Kollat, Jana; Brieger, Steven A.
This paper investigates differences between nascent and established entrepreneurs with regard to their ventures' environmental orientation. Based on quantitative data of more than 10, 000 entrepreneurs, analyses of variance (ANOVA) are conducted. The results show that the average environmental orientation is significantly higher among nascent than among established entrepreneurs. Variables are identified which influence the magnitude of these differences, as they exert different effects on environmental orientation among nascent and established entrepreneurs, such as household income or media reports. Based on the findings, implications for policymakers, entrepreneurs as well as for entrepreneurship education are drawn to use the potential of nascent environmental entrepreneurs more comprehensively. For instance, teaching institutions need to give realistic impressions of the challenges and potentials of environmental entrepreneurship. Similarly, environmental entrepreneurs should think about the specific challenges connected with environmentally-oriented ventures, such as potential trade-offs between environmental and economic objectives, at early stages of their entrepreneurial activity.